'Why Stant this Word Heere': Text, Gloss, and Voice in Hoccleve's 'Remonstrance to Oldcastle'. (27th May 2022) - Griffiths, Jane
Abstract: This article is concerned with reading in Hoccleve's 'Remonstrance to Oldcastle' (c. 1415), specifically with the way in which what the poem says about reading contrasts both with other aspects of Hoccleve's advice and with the kind of reading that is encouraged by its mise-en-page. In his attempt to counter Oldcastle's heretical beliefs, Hoccleve twice counsels against engaged, interpretative reading: first in his praise of the orthodox family who avoid textual criticism of Scripture; second in the famous passage where he advises Oldcastle to read romance rather than the Bible. The article argues that the glossing of the poem nonetheless encourages very active engagement with Hoccleve's own text, that such engaged reading reveals his remonstrance to be directed at Henry V as much as Oldcastle, and that the programme of supposedly innocuous reading that he suggests for Oldcastle is one of the points where this is most apparent. Paying close attention both to Hoccleve's sources and to the form in which the text appears in MS HM 111, it demonstrates that every aspect of the text begs the question that Hoccleve encourages Oldcastle not to ask: 'Why stant this word heere?'